The Influence of Islamic Knowledge of Muslimah Clothing, Hijab-Fashion Influencers, and Modern Hijab-Clothing Style toward Hijabers' Fashion Consciousness and Its Impact on Hijabers' Choice of Hijab-Clothing Style among Hijabers in Pontianak - B1024151022, Gadis Meisantika Atmaja (Jurnal Manajemen Update, 2020)
ABSTRACTThe purpose of this research is to analyze the influence of Islamic knowledge of Muslimah clothing, Hijab-Fashion Influencers, and modern hijab-clothing style toward Hijabers’ Fashion Consciousness and its impact on Hijabers’ choice of hijab-clothing choice among Hijabers in Pontianak. The rising numbers of hijab-fashion influencers on Instagram may rise Hijabers’ consciousness to be more fashionable in dressing. And so is the development of hijab-clothing style the are made more modernly with various designs, eye-catching colors, and completed with accessories that supports Hijabers’ fashionable modern look. However, hijab-clothing is supposed to be in line with the principles of Islam on how a Muslimah should properly dress, because the regulations regarding hijab-clothing itself is already written in the Holy Quran.This researchis a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 150 samples who fulfill the requirements. The samples of this research are Hijabers in Pontianak who are in range of age from 18-35 years old and are having Instagram account that is following Hijab-Fashion Influencers. In this research, the data analysing method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1: There is negative relationship between Islamic Knowledge of Muslimah Clothing and Hijabers’ Fashion Consciousness, H2: There is positive relationship betweenHijab-Fashion Influencers and Hijabers’ Fashion Consciousness, H3: There is positive relationship betweenModern Hijab-Clothing Style and Hijabers’ Fashion Consciousness, H4: There is significant relationship between Hijabers’ Fashion Consciousness and Hijabers’ Choice of Hijab-Clothing Style. The result of this research shows that H3 and H4 are accepted but H1 and H2 are rejected Keywords: Islamic knowledge of muslimah clothing, hijab-fashion influencers, modern hijab-clothing style, fashion consciousness, choice of hijab-clothing style, hijaber BibiographyAbidin, C. (2016). 'Aren’t These Just Young, Rich Women Doing Vain Things Online?': Influencer Selfies as Subversive Frivolity. Social Media + Society, Vol. 2 Issue 2 , 1-17.Ali, I., & Sohail, B. (2018). Impact of Fashion Consciousness on Hijabistas’ Buying Behavior . Journal of Philosopgy, Culture, and Religion, Vol. 38 , 56-63.Freberg, K., Graham, K., McGaughey, K., & Freberg, L. A. (2011). Who Are The Social Media Influencers? A Study of Public Perceptions. Public Relations Review , 90-92.Gutman, J., & Mills, M. K. (1982). Fashion Life Style, Self-Concept, Shopping Orientation, and Store Patronage: An Integrative Analysis. Journal of Retailing, Vol. 58, Issue 2 , 64.Hassim, N. (2014). A Comparative Analysis on Hijab Wearing in Malaysian Muslimah Magazines. The Journal of the South-East Asia Research Center for Communication and Humanities, Vol. 6, Issue 1 , 79-96.Indarti, & Peng, L. H. (2016). Modern Hijab Style in Indonesia as An Expression of Cultural Identity and Communication. 2016 International Conference on Applied System Innovation (ICASI). Okinawa: Institute of Elctrical and Elctronics Engineers.Izea. (2017, May 2). Influencer Marketing. Retrieved August 3, 2019, from IZEA: https://izea.com/2017/05/02/what-is-an-instagram-influencer/Khater, A. F. (2010). Source in the History of the Modern Middle East. Boston: Wadsworth.Milewski, J. A. (2005). Fashion and the Culture of Consumption: Perceptions of Fashion Trends Among College Students. New York: SUNY Buffalo.O'cass, A., Lee, W. J., & Siahtiri, V. (2013). Can Islam and Status Consumption Live Together in the House of Fashion Clothing? Vol. 17 Issue 4. Journal of Fashion Marketing and Management , 440-459.Report, S. o. (2016). State of The Global Islamic Economy Report. New York: Thomson Reuters.Report, S. o. (2018). State of The Global Islamic Economy Report. New York: Thomson Reuters.Shihab, Q. (2012). Jilbab, Pakaian Wanita Muslimah: Pandangan Ulama Masa Lalu dan Cendikiawan Kontemporer. Tangerang Selatan: Lentera Hati Group.Utami, V., Maulida, E., Nurbaeti, E., & Cholilawati. (2018). Muslim Fashion Trends: Analysis and Perspective. 3rd UNJ International Conference on Technical and Vocational Education and Training 2018 (pp. 596-602). Jakarta: Knowledge E.